Insights into membrane translocation of the cell-penetrating peptide pVEC from molecular dynamics calculations - SARIYAR AKBULUT, BERNA (TAYLOR & FRANCIS INC, 2016)
Discovery of cargo carrying cell-penetrating peptides has opened a new gate in the development of peptide-based drugs that can effectively target intracellular enzymes. Success in application and development of cell-penetrating peptides in drug design depends on understanding their translocation mechanisms. In this study, our aim was to examine the bacterial translocation mechanism of the cell-penetrating pVEC peptide (LLIILRRRIRKQAHAHSK) using steered molecular dynamics (SMD) simulations. The significance of specific residues or regions for translocation was studied by performing SMD simulations on the alanine mutants and other variants of pVEC. Residue-based analysis showed that positively charged residues contribute to adsorption to the lipid bilayer and to electrostatic interactions with the lipid bilayer as peptides are translocated. Translocation takes place in three main stages; the insertion of the N-terminus into the bilayer, the inclusion of the whole peptide inside the membrane and the exit of the N-terminus from the bilayer. These three stages mirror the three regions on pVEC; namely, the hydrophobic N-terminus, the cationic midsection, and the hydrophilic C-terminus. The N-terminal truncated pVEC, I3A, L5A, R7A mutants and scramble-pVEC make weaker interactions with the lipids during translocation highlighting the contribution of the N-terminal residues and the sequence of the structural regions to the translocation mechanism. This study provides atomistic detail about the mechanism of pVEC peptide translocation and can guide future peptide-based drug design efforts.
Keywords: steered molecular dynamics; cell-penetrating peptide; pVEC; uptake mechanism; LIPID-BILAYERS; TAT PEPTIDE; SIMULATIONS; MECHANISMS; INSERTION; KINETICS; DELIVERY; DESIGN